Managing flood risk in fetch-limited environments - Carrasco, Ana Rita (2017)
There is little unanimity concerning the environmental modifications potentially forced by the acceleration of global climate change in the coming century, or the future actions required to work towards a sustainable development of natural habitats in the coastal zone. A simple framework to assess the potential implications of flooding in fetch-limited coastal environments (with no relevant wave setup), experiencing both coastal and river flooding, was recently developed. It identifies tide, storm surge, sea level rise and river discharge as the main sources of flooding hazards. Hazard maps differentiate distinctive zones of flooding: the constantly flooded zone, the frequently flooded zone, and the infrequently flooded zone. The framework prioritizes site-based local management, and identifies alternative tools for sustainable coastal resources, to face non-desired flood effects. It was applied to a morphologically complex (tidal channels network, salt marshes, dunes) occupied backbarrier coastal stretch located in Culatra Island, South Portugal (max. fetch ~ 4 km). The obtained inundation levels predicted for 1, 10 and 100 year-return periods were 2.02 m, 2.39 m, and 2.84 m above MSL, respectively. The high-, moderate-, and low-risk zones include about 34 m2 , 1,073 m2 and 31,821 m2 of occupied area, respectively. Besides houses, flood impacts also affect other infrastructures (e.g., walkways and recreational structures). Several best practices principles and guidelines were proposed for the three risk zones, namely the adaptation to uses with ‘added value’, which enhances the local ecological values and strengths economic activities. This study contributes to the method validation at a complex morphological area and enriches the understanding about the potential of flood in fetch-limited conditions, praising the perspective of ‘living with climate change’.